2007
DOI: 10.1111/j.1469-0691.2007.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of trehalose in resistance to macrophage killing: study with a tps1/tps1 trehalose-deficient mutant of Candida albicans

Abstract: Accumulation of trehalose by yeast is an important protective mechanism against different stress conditions. This study examined the effect of trehalose on several growth features, as well as its association with the intracellular survival of yeasts exposed to macrophages. A tps1/tps1 mutant and its parental counterpart, CAI4, exhibited similar growth rates and preserved their dimorphic conversion and agglutination ability. However, electron-microscopy of cell-wall architecture showed a partial loss of materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 38 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…5). Recently it has been shown that mutants with a deletion of TPS1, encoding the first enzyme of the trehalose biosynthesis pathway, are more easily killed by macrophages than wild-type control cells (23).…”
Section: Vol 76 2008 Combined Inactivation Of C Albicans Gpr1 and mentioning
confidence: 99%
“…5). Recently it has been shown that mutants with a deletion of TPS1, encoding the first enzyme of the trehalose biosynthesis pathway, are more easily killed by macrophages than wild-type control cells (23).…”
Section: Vol 76 2008 Combined Inactivation Of C Albicans Gpr1 and mentioning
confidence: 99%
“…Little is known about the mechanisms by which A. fumigatus survives under these conditions. One possible mechanism by which A. fumigatus adapts to environmental stress is via the biosynthesis of the carbohydrate trehalose, which is involved in mediating the stress response and virulence of other pathogenic fungi such as Candida albicans and Cryptococcus neoformans (1,22,30,48). The trehalose content of these fungal cells may increase up to 50-fold in response to oxidative stress, osmotic stress, and heat shock (27).…”
mentioning
confidence: 99%
“…In the pathogenic yeasts C. albicans and C. neoformans, the single-copy trehalose-6-phosphate synthase Tps1 is required for normal oxidative stress response and hyphal development and has a role in mediating virulence (1,22,30,48). In Aspergillus nidulans, the trehalose-6-phosphate synthase TpsA is necessary for normal fungal development, thermosensitive growth and response to sublethal exposure to oxidative stress (16).…”
mentioning
confidence: 99%
“…Biosynthesis of trehalose also provides protection against oxidant stress (4,27,41). Of the mitogen-activated protein kinase (MAPK) signal pathways that regulate new gene transcription during stress, the MKC1 MAPK and HOG1 MAPK (for hyperosmotic glycerol) pathways are prominent in a number of yeasts and filamentous fungi in regard to adaptation to hyperosmotic and/or oxidant stress (2, 3, 5, 6, 11, 12, 18-21, 29, 44, 50, 52, 55).…”
mentioning
confidence: 99%